CHEMICAL AND BIOLOGICAL ASPECTS OF CAROTENOIDS - Adizova Shoira Toirovna , (TADQIQOTLAR.UZ, 2024)
The structure and biological functions of carotenoids are considered with an emphasis on xanthophylls, which have been of the greatest interest lately. The diverse biological activity of carotenoids determines the importance of these compounds in food design programs.